EVALUASI DAN PERBAIKAN UI/UX WEBSITE INVITEES MENGGUNAKAN METODE HUMAN CENTERED DESIGN - Gisella Beatrice Ticoalu; Izmy Alwiah Musdar; Abdul Munir S. (STMIK KHARISMA Makassar, 2023)
User Interface (UI) and User Experience (UX) are important things to ensure the Invitees website can meet the needs of its users. In addition, an attractive and understandable interface will be the main attraction for potential users. This study used the Human-Centered Design (HCD) method and involves a System Usability Scale (SUS) questionnaire distributed to 30 respondents for the initial UI/UX evaluation of the Invitees website and evaluation of the solution design after repair. From the results of the first evaluation, an average SUS score of 77.08 was obtained, which means that it is still acceptable to users. Then solution designs are made to improve some parts of the website according to the suggestions received from respondents also to increase the SUS score. The results of the evaluation of the solution design obtained an average score of 80.75 which means that there was an increase in the usability value after improvements were made according to the Human-Centered Design (HCD) method.